The Prevalence and Risk Factors of Hypokalemia in Pregnancy-Related Hospitalizations: A Nationwide Population Study - Chien-Wen Yang; Si Li; Yishan Dong (International Journal of Nephrology)
Background. There are no nationwide population studies conducted to analyze the prevalence and risk factors associated with hypokalemia during pregnancy in the U.S. Method. We retrieved data from the Nationwide Inpatient Sample (NIS) and the National Inpatient Sample of Healthcare Cost and Utilization Project (HCUP) for pregnant patients with hypokalemia from 2012 to 2014. We used a chi-squared test to analyze categorical variables and an adjusted Wald test to compare quantitative variables. We applied logistic regression models to calculate adjusted odds ratios (ORs) with 95% confidence intervals (95% CIs) to identify the risk factors for hypokalemia. We used a p value <0.05 as the cutoff for statistical significance. Result. Among 12,431,909 pregnancy-related discharges, females of younger age (mean age 27.0 ± 6.2 vs. 28.1 ± 6.0, p<0.001), of African American race, using government-paid insurance, with an income level in the first quartile, and of a higher Charlson Comorbidity Index score (≥1) were found to have a higher likelihood of hypokalemia during pregnancy (p<0.001). Gestational hypertension (GH) (including pre-eclampsia and eclampsia, aOR 2.03, 95% CI 1.94–2.12, p<0.001), hyperemesis gravidarum (aOR 33.18, 95% CI 31.61–34.83, p<0.001), and post-partum hemorrhage (aOR 1.42, 95% CI 1.31–1.53, p<0.001) were found to be independently associated with a higher rate of hypokalemia during pregnancy. Conclusion. The prevalence of hypokalemia during pregnancy was less than 1% in this large, nationwide population-based study. There were significant differences between those patients who developed hypokalemia during pregnancy. Notably, those who had hypokalemia were younger, of African American race, and of a low-income level. Congestive heart failure, coronary artery disease, Cushing’s syndrome, GH, and hyperemesis gravidarum were found to be associated with hypokalemia during pregnancy.